MEMBANGUN KARAKTER RELIGIUS SISWA SEKOLAH DASAR MELALUI PEMBIASAAN TADARUS AL-QUR’AN - Dyah Ayu Puji Lestari; Santy Dinar Permata; Anwas Mashuri (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
The formation of the character of students can be done through habituation or school culture as it has become the grand design of character education. School culture plays an important role in instilling character education values, especially in schools. This study aims to determine the effect of habituation of Al-Qur'an tadarus on the religious character cultivation of students at SDN Brangol 1. This research uses quantitative methods with ex post facto techniques. The population in this study were all students of SDN Brangol 1, totaling 78 people, and the sample of this study was 26 people using a purposive sampling technique. The research instrument used a questionnaire prepared by the researcher. Hypothesis analysis of this study uses a simple linear regression test. Because the value of to 3.522 > tt 2.064, it can be concluded that the habit of reciting the Al-Qur'an affects the religious character of students at SDN Brangol 1.